Pregnant women’s awareness, knowledge and beliefs about pelvic floor muscles: a cross-sectional survey - Hill, Anne-Marie; McPhail, S.; Wilson, J.; Berlach, R. (2017)
Introduction and hypothesis: Pregnant women benefit from completing pelvic floor muscle exercises (PFMEs). The aims of the study were to evaluate pregnant women’s levels of awareness, knowledge, and beliefs about the pelvic floor muscles (PFMs) and PFMEs. Methods: A cross-sectional survey was conducted. Respondents were pregnant women over the age of 18 years who attended antenatal clinics in Western Australia (WA). Questionnaire items measured awareness and knowledge about PFMs, confidence and beliefs about engaging in PFMEs, and attendance at antenatal education (ANE) classes. Chi-squared tests examined potential associations between questionnaire items and respondent characteristics. Results: Mean gestation of respondents (n = 633 out of 850; 74% response rate) was 28.7 (+7.8) weeks and 50% were giving birth for the first time. Although 76% of respondents knew that PFMs can prevent urinary incontinence, only 27% knew that they prevented faecal incontinence and 41% thought it was normal to leak urine when pregnant. Only n = 72 (11%) were practicing PFMEs. Respondents who had attended ANE (28%) were significantly more knowledgeable about pelvic floor function (p < .001) and significantly less likely to believe that leaking urine during pregnancy was normal (p = 0.02), compared with those who had not attended ANE. Respondents who did not speak English at home (18%) were significantly less knowledgeable about PFMs and PFMEs, and significantly less likely to have attended, or planned to attend, ANE classes. Conclusion: Pregnant women require more health education regarding PFMs. Education should be provided using diverse modes, especially for women from migrant backgrounds and women who do not plan to attend formal ANE classes.